2020
DOI: 10.1039/d0nj03912h
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular chiral surface of nickel sulfate hexahydrate crystals and its ability to chirally recognize enantiomers by adsorption data

Abstract: The chiral recognition ability of the surface of α-NiSO4·6H2O was found using gas and liquid chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…This means that the formation of the layers of limonene enantiomers was different. This corresponds to the results of adsorption isotherm analysis on cytosine 23 and nickel sulfate hexahydrate, 24 in which enantiomorphic crystals do not recognise individual molecules of enantiomers, but a layer of enantiomers on their surface. Since limonene–limonene interactions were stronger than limonene–crystal surface interactions, the formation of a second layer may begin before the crystal surface was covered by the first layer.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…This means that the formation of the layers of limonene enantiomers was different. This corresponds to the results of adsorption isotherm analysis on cytosine 23 and nickel sulfate hexahydrate, 24 in which enantiomorphic crystals do not recognise individual molecules of enantiomers, but a layer of enantiomers on their surface. Since limonene–limonene interactions were stronger than limonene–crystal surface interactions, the formation of a second layer may begin before the crystal surface was covered by the first layer.…”
Section: Resultssupporting
confidence: 75%
“…Thus, the maximum difference in adsorption values was 3.5%. In general, the enantioselectivity provided by porous polymers modified with hippuric acid and phloroglucinol is lower than that of previously studied samples modified with nickel sulfate hexahydrate 24 and cytosine. 23 The isotherms also differed in their shape, as shown in Fig.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…This differed from the previously studied nonporous chiral crystals. 7,8,10 For such crystals the enantiomer isotherms differed only in the nonlinear region. This was caused by the mandatory formation of an adsorption layer on the adsorbent surface for supramolecular chiral recognition.…”
Section: Resultsmentioning
confidence: 99%
“…A different adsorption of enantiomers was found on crystals with a supramolecular chiral surface, obtained from achiral precursors. 7–10 Examples of enantiomorphic crystals are retgersite, cytosine, hippuric acid, phloroglucinol, CsCuCl 3 , γ-glycine, and others. 11–14 It was found that the recognition of enantiomers by the supramolecular chiral surface of non-porous crystals is observed only in the region of high surface coverage.…”
Section: Introductionmentioning
confidence: 99%